2021
DOI: 10.1007/s00894-021-04954-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bilayer B50, B52, B56, and B58: structural evolution in bilayer B48–B72 clusters

Abstract: The successive experimental observations of planar, cage-like, seashell-like, and bilayer B n -/0 clusters in the size range between n = 3-48 well demonstrate the structural diversity and rich chemistry of boron nanoclusters. Based on extensive global minimum search and density functional theory calculations, we predict herein the bilayer C 1 B 50 (I), C 2h B 52 (II), C 1 B 56 (IV), and C 2v B 58 (V) as the global minima of the systems to ll in the missing gap in the bilayer B 2n series between B 48 -B 72 . Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
(33 reference statements)
3
16
0
Order By: Relevance
“…The BL B 84 –B 98 species discussed above also turn out to be highly dynamically stable during extensive BOMD simulations, as demonstrated in the cases of high-symmetry C 2 v B 86 ( II ) and C 2 v B 96 ( VII ) in Fig. S4† which have the small average root-mean-square-deviations of RMSD = 0.15 and 0.12 Å and maximum bond length deviations of MAXD = 0.79 and 0.66 Å at 1000 K and 700 K, respectively, similar to the situations in the previously reported BL B 48 –B 72 12,23–25 series. No lower-lying isomers were observed during MD simulations in 30 ps.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The BL B 84 –B 98 species discussed above also turn out to be highly dynamically stable during extensive BOMD simulations, as demonstrated in the cases of high-symmetry C 2 v B 86 ( II ) and C 2 v B 96 ( VII ) in Fig. S4† which have the small average root-mean-square-deviations of RMSD = 0.15 and 0.12 Å and maximum bond length deviations of MAXD = 0.79 and 0.66 Å at 1000 K and 700 K, respectively, similar to the situations in the previously reported BL B 48 –B 72 12,23–25 series. No lower-lying isomers were observed during MD simulations in 30 ps.…”
Section: Resultssupporting
confidence: 81%
“…1) with two staggered B 6 hexagonal holes on the top and bottom layers. 14,23–25 The formations of five interlayer B–B σ-bonds between the top and bottom layers and two staggered B 6 hexagonal holes on the top and bottom layers effectively help to stabilize the system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3–8 The newly discovered bilayer motif has been recently extended to a large size range of even numbered neutral boron clusters between B 48 –B 72 at density functional theory (DFT) level. 9–11 Ion mobility and theoretical calculations, on the other hand, showed that B n + monocations possess tubular structures in the size range n = 16–25. 12 Perfect cage-like B 80 has also been proposed at density functional theory (DFT) 13,14 level which was later found to favor core–shell structures in thermodynamics.…”
Section: Introductionmentioning
confidence: 99%